Construction of amorphous Ni(OH)2@nickel nanowire with interconnected structure as advanced core-shell electrodes for asymmetric supercapacitors. (October 2020) - Ge, Wei; Encinas, Armando; Ruiz, Maria Fernanda; Song, Shaoxian
Highlights: INWA acts as both a miniature conductive scaffold and highly conductive core. The amorphous Ni(OH)2 @INWA possesses high electronic and ionic conductivities. The amorphous Ni(OH)2 @INWA presents ultrahigh specific capacitances of 3400 and 3000 F g −1 at 5 and 100 A g −1, respectively. Abstract: Amorphous Ni(OH)2 closely coating on interconnected nickel nanowire arrays (Ni(OH)2 @INWA) with rational architectures were prepared. The INWA with small wire diameter and high wire density acts both as miniature conductive scaffold and highly conductive core providing large surface area to load amorphous Ni(OH)2 and ensuring high ionic/electronic conductivities. The amorphous Ni(OH)2 nanosheets in-situ converted from the metallic surface of INWA are in seamless contact with the metallic core forming a close core-shell structure. Because of the material and architecture advantages, the amorphous Ni(OH)2 @INWA presents enhanced electrochemical performance of ultrahigh specific capacitances of 3400 F g −1 at a specific current of 5 A g 1, remarkable rate capability (3000 F g −1 at 100 A g −1 ). The asymmetric supercapacitor of Ni(OH)2 @INWA//reduced graphene oxide delivers a high specific energy of 53 Wh kg 1 at a specific power of 395 W kg −1, and a specific energy of 31 Wh kg −1 can be maintained at a specific power of 4973 W kg −1 . It also shows a long-term stability with 91 % retention of the initial capacitance after 10000 cycles at a specific current of 2 A g −1 . Graphical abstract: Image, graphical abstract